2006
DOI: 10.1128/mcb.26.4.1170-1182.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Is Required for Ras-Induced Oncogenic Transformation

Abstract: Most human cancers involve either mutational activation of the Ras oncogenic pathway and/or inactivation of the retinoblastoma tumor suppressor (RB) pathway. Paradoxically, tumors that harbor Ras mutations almost invariably retain expression of a wild-type pRB protein. We explain this phenomenon by demonstrating that Ras-induced oncogenic transformation surprisingly depends on functional pRB protein. Cells lacking pRB are less susceptible to the oncogenic actions of H-Ras V12 than wild-type cells and activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 77 publications
5
51
0
1
Order By: Relevance
“…Thus, these findings suggest that there are intrinsic physiological conditions under which loss of RB does not provide a clear advantage to tumor cells. Interestingly, recent literature has suggested a surprising requirement for RB in Rasmediated transformation (Williams et al, 2006). This role for RB seems counterintuitive given the previously documented role for RB deficiency in promoting escape from facets of Ras-mediated senescence (Serrano et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these findings suggest that there are intrinsic physiological conditions under which loss of RB does not provide a clear advantage to tumor cells. Interestingly, recent literature has suggested a surprising requirement for RB in Rasmediated transformation (Williams et al, 2006). This role for RB seems counterintuitive given the previously documented role for RB deficiency in promoting escape from facets of Ras-mediated senescence (Serrano et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that oncogenic transformation through Ras in cell culture and animal models is dependent on cyclin D1 (Liu et al, 1995;Peeper et al, 1997). Therefore, it was suggested that these two pathways function in parallel, although recent studies have proposed that loss of RB actually compromises Ras-mediated transformation and proliferation of tumor cells (DeGregori, 2006;Williams et al, 2006). Thus, these contradictory findings suggest that further probing the intersection of oncogenic signaling and RB function may yield important insights into cooperation between coordinated tumorassociated events in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Still, it is unclear why different paths to cancer preferentially select for mutations in one component over another. A paper in this issue of Molecular Cellular Biology by Williams, Classon, and colleagues reveals a surprising requirement for Rb in proliferation and transformation mediated by the Ras oncogene (50). This study provides a rationale for why mutational activation of Ras and genetic disruption of Rb are rarely found together in human cancers.…”
mentioning
confidence: 92%
“…Williams and colleagues now shed light on this issue (50). They demonstrate that, quite in contrast to Rb's usual tumor suppressor role and in marked contrast to p107/p130 loss, Rb loss actually impedes the transformation of mouse NIH 3T3 fibroblasts by Ras*.…”
mentioning
confidence: 99%
See 1 more Smart Citation